Anticipated Suicide Stigma, Secrecy, and Suicidality among Suicide Attempt Survivors. Issue 3 (3rd February 2020) - Mayer, Lea; Rüsch, Nicolas; Frey, Laura M.; Nadorff, Michael R.; Drapeau, Chris W.; Sheehan, Lindsay; Oexle, Nathalie
Abstract : Objective: Suicidal behavior is stigmatized, and suicide attempt survivors often keep their experiences secret. Although secrecy can protect from discrimination, research from related fields suggests that both the experience of stigma and secrecy can contribute to suicidality. Although suicide attempt survivors are at high risk for reattempt, research investigating the link between suicide stigma and suicidality among this group is rare. Method: A community sample of 159 suicide attempt survivors participated in an online survey in the US. We used multiple linear regression models to test the association between anticipated suicide stigma and current suicidality, as well as a path model to test the mediating effect of secrecy. Results: After controlling for age, sex, number of lifetime suicide attempts, and time since the most recent suicide attempt, anticipated suicide stigma was significantly associated with increased suicidality. In a controlled path model, this link was partially mediated by increased secrecy. Conclusion: These results provide initial support that anticipated suicide stigma, and secrecy can contribute to suicidality among suicide attempt survivors. Therefore, programs to support suicide attempt survivors in coping with suicide stigma and secrecy, as well as interventions to reduce harmful aspects of public suicide stigma, could contribute to suicide prevention.